Basics of grinding (Fundamental manufacturing processes, 2000)
Grinding is a material removal process used to shape and finish high precision workpieces made from metals and nonmetals. To provide a broad understanding of grinding and its fundamental components, this videotape examines : the four primary grinding processes, abrasives and grinding wheels, balancing, trueing and dressing grinding wheels, grinding safety and workpiece surface finish. This videotape concludes with a review to reinforce the material it outlines.